Are AI Health Predictions Truly Confidential? Navigating the Legal and Ethical Labyrinth - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The integration of Artificial Intelligence AI into healthcare is rapidly transforming diagnostics, treatment planning, and predictive medicine. AI models, tr...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics